(untitled) (Andamios, Revista de Investigación Social, 2008)
The notion of “writing”, as it was developed chiefly by the French critics, Maurice Blanchot and Roland Barthes since the decade of the 50’s, deeply transforms the domain of literary studies: the philosophical and semiotical ground of these reflections involves a radical change of the point of view on language, rhetoric, and even the object and sense of the analysis itself. The concepts built upon this convergence of different disciplines makes it possible to foster new expectations and reveals another relevance for the reflection on literature. This text seeks to explore the contemporary developments of the notion of writing since the introduction of the notion of negative semiotics and the radical approaches on the relation of reading and rhetoric in the perspective of literary criticism.